Higher Education, Happiness, and Residents' Health - Tan, Hong; Luo, Jin; Zhang, Ming (Frontiers in Psychology, 2020)
The study proposes a new mechanism by which higher education affects the health of residents, showing that higher education can first improve the happiness of residents and then improve their health. In this research, we employ the data collected in Chinese General Social Survey in 2013 and adopt the semiparametric estimation methodology of ordered probit model. Our main findings include the following. First, compared with the residents without higher education, residents with high education enjoy better health conditions, and residents' happiness also significantly affects their health conditions. Second, higher education may have a long-term impact on residents' health by affecting their happiness. Third, the results of grouping test demonstrate that, with the increase in age, the influence of residents' happiness on health is more pronounced, but the mechanism of higher education to improve health status by improving residents' happiness becomes unobvious. Furthermore, we adopt the Shapley value decomposition methodology to decompose the effects of various factors on residents' health. We find that with the increase in age, happiness contributes more and more to residents' health conditions.